2020
DOI: 10.1039/c9ce01548e
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the non-covalent Pb⋯S and S⋯S interactions in the solid-state structure of a hemidirected lead(ii) complex

Abstract: A hemi-directed copper(ii)/lead(ii) complex has been synthesized and characterized. The energy of chalcogen–chalcogen and tetrel bonding interactions in this complex was analyzed by DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…Large loops created by the [Pb 2 (sdc) 2 ] units act as wheels , and long spacer bpp ligands act as axles and are responsible for the doubly entangled 2D polyrotaxane structure (Figure d). ,,, The Pb­(II) center is five-coordinated with a hemispherical coordination mode, being bound to four carboxylate oxygen atoms from three sdc ligands and one pyridine nitrogen from the bpp ligand (Figure b,e). The unusual secondary building unit (SBU) could be attributed to the hemispherical coordination of the two Pb­(II) centers with the stereochemical activity of the lone 6 s 2 pair. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…Large loops created by the [Pb 2 (sdc) 2 ] units act as wheels , and long spacer bpp ligands act as axles and are responsible for the doubly entangled 2D polyrotaxane structure (Figure d). ,,, The Pb­(II) center is five-coordinated with a hemispherical coordination mode, being bound to four carboxylate oxygen atoms from three sdc ligands and one pyridine nitrogen from the bpp ligand (Figure b,e). The unusual secondary building unit (SBU) could be attributed to the hemispherical coordination of the two Pb­(II) centers with the stereochemical activity of the lone 6 s 2 pair. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…According to Mirdya et al, the S…S interaction within the dimer is due to the overlap of a filled 3p orbital of the sulfur atom of one dimer and an empty σ* anti‐bonding orbital of the sulfur atom of another dimer. The S…S estimated stabilization energy is 0.34 kcal mol −1 computed at the B3LYP/ Lanl2DZ/6‐31G(d) level of theory using NBO analysis 61 . CCSD(T)/CBS quantum chemical calculations showed that S…S interaction stabilize the parallel orientation in crystal structures up to 1.8 kcal mol −1.…”
Section: Reactivitymentioning
confidence: 98%
“…Consequently, SCN − ligand-derived CPs with intriguing architectural frameworks have recently attracted much attention in coordination chemistry (Scheme S1A and B †). [11][12][13][14][15][16][17][18][19][20][21][22] The attraction is due to the diverse bonding functionalities in their X-ray crystal structures. In this way, the fruitful synthesis of CPs using compartmentalized N 2 O 4 scaffolds stands out due to its convenient synthesis, product stability, and versatility.…”
Section: Introductionmentioning
confidence: 99%